CORRELATION OF BODY MASS INDEX, AGE AND GENDER WITH THE DEGREE OF SPONDYLOLISTHESIS ON LUMBOSACRAL XRAY PHOTOS AT HAJI ADAM MALIK HOSPITAL MEDAN - Dina Utami Lubis; Evo Elidar Harahap; Kiki Mohammad Iqbal (PT. Radja Intercontinental Publishing, 2024)
Introduction :Spondylolisthesis is a displacement of one vertebra relative to the vertebra below it with an estimated prevalence of spondylolisthesis of 6 to 7% at age 19 years, and up to 18% of adult patients undergoing MRI of the lumbar spine. Grade I spondylolisthesis accounts for 75% of all cases. Various factors can influence the occurrence of spondylolisthesis such as BMI, age and gender. Objective. This study aims to determine the characteristics and analysis of the relationship between spondylolisthesis patients and lumbosacral x-rays based on body mass index, age and gender as well as the local anatomical distribution and frequency of spondylolisthesis degrees. Results :A total of 120 patients were predominantly aged>60 years old, female and obese. Based on the location of spondylolisthesis, most of them are at L4-5. There are almost the same numbers of scoliosis patients and those without scoliosis. The majority of spondylolisthesis patients are dominated by spondylosis on lumbosacral xray examination. There was a relationship between spondylolisthesis and age, BMI and gender (p<0.05). Spondylolisthesis patients with female risk factors are at risk of experiencing spondylolisthesis (OR=6.490) and obese patients are at risk of experiencing spondylolisthesis (OR=4.024). Discussion:The prevalence of spondylolisthesis and patient gender may be related to the influence of the female sex hormone estrogen on tissues associated with the human musculoskeletal system. An increase in body mass index (BMI), an axial load on the intervertebral discs and facet joints, causes an increase in compressive forces on the spine. Age has the potential to be a determining factor in degenerative conditions with the occurrence of disc narrowing, osteoarthritis (OA) of facet joints, and degenerative spondylolisthesis showing a significant linear trend. Conclusion :There is a significant relationship between spondylolisthesis and BMI, age and gender in spondylolisthesis patients who underwent lumbosacral xray examination at H Adam Malik Hospital Meda. The variables gender and BMI are the most significant risk factors. Spondylolisthesis patients with female risk factors are at risk of experiencing spondylolisthesis 6.5 times greater and patients who have an obese BMI are at risk of experiencing spondylolisthesis 4 times greater than patients without this condition at RSUP H Adam Malik Medan.